Monitoring exposure to propylene oxide through the determination of hemoglobin alkylation. - Osterman-Golkar, S; Bailey, E; Farmer, P B; Gorf, S M; Lamb, J H (Scandinavian Journal of Work, Environment & Health, 1984)
The levels of Nt-(2-hydroxypropyl)histidine in hemoglobin were determined for eight employees of a plant where propylene oxide is used and for thirteen referents. Good agreement was obtained between the estimated exposure and the degree of alkylation of hemoglobin; values of 0.1 nmol (11 referents), 0.2 nmol (1 referent), 0.38 nmol (1 referent), 0.2 nmol (1 employee without exposure), 0.85-1.2 nmol (3 employees with low-intermediate exposure), and 4.5-13 nmol (4 employees with high exposure; 10 ppm propylene oxide during 25-75% of the work time) per gram of hemoglobin were recorded. The method gives a measure of the in vivo dose obtained during a period of about four months and is therefore superior to point measurements of concentrations for the surveillance of exposure conditions in work environments.